2021
DOI: 10.23887/jpbi.v9i1.32518
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Preparation of Lesson Plan and Constraints in English as a Foreign Language During the Pandemic Outbreak in the Junior High School

Abstract: Teaching English online is considered problematic. The availability of a support system and internet quota is the main obstacle. This has an impact on the low ability of students. The purpose of this study is to analyze the abilities and constraints of teachers in preparing lesson plans and student obstacles in EFL learning through Google Meet during the Covid-19 pandemic. The sample of this research is a seventh-grade EFL teacher and also 60 seventh-grade junior high school students. The design applied is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Meanwhile, some previous studies have been added to enrich the present study. Wulandari et al, (2021) undertook the previous study that focused on exploring the teacher's capability and limit in preparing lesson plans and barrier factors of the foreign language learner in the learning process adopting Google Meet during the pandemic. The result showed that teachers struggle to create lesson plans because they have less capability and face several challenges when selecting learning strategies, choosing instruments and evaluation, and learning media.…”
Section: What Are the Efl Teacher's Strategies In Preparing Classroom...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, some previous studies have been added to enrich the present study. Wulandari et al, (2021) undertook the previous study that focused on exploring the teacher's capability and limit in preparing lesson plans and barrier factors of the foreign language learner in the learning process adopting Google Meet during the pandemic. The result showed that teachers struggle to create lesson plans because they have less capability and face several challenges when selecting learning strategies, choosing instruments and evaluation, and learning media.…”
Section: What Are the Efl Teacher's Strategies In Preparing Classroom...mentioning
confidence: 99%
“…There are several studies related to this research. The first study conducted by Wulandari, Tantra, and Santosa (2021) analyzes the teacher's ability to prepare a lesson plan and students' obstacles in online learning. This mixed method study revealed that the teachers are less capable and encounter several challenges when it comes to adopting a type of technique, an instrument, assessing a technique, or selecting instructional media.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the implementation of lesson plans, the English teacher used a one-sheet lesson plan in which the contents were simplified (Abidah et al, 2020). Some benefits of this lesson plan are fostering flexibility, creativity, and innovation in the EFL classroom regarding learning media, materials, assessments and evaluation (P. D. M. Wulandari et al, 2021).…”
Section: The Preparation Stage Of E-learningmentioning
confidence: 99%
“…Electrical impulses move through the nervous system's intricate circuitry (Fauzi, Ambi, Madaud, & Unin, 2022). The internal organs are told to speed up or slow down their activity by a set of hormones found throughout the circulation (Wulandari, Tantra, & Santosa, 2021). Psychologists that investigate perceptions (Fauzi et al, 2022), memories, and behavior from a biological perspective look at how physical events interact with events in the outside world to form perceptions, memories, and behavior (Zainal & Yunus, 2022).…”
Section: Introductionmentioning
confidence: 99%